Inter-Organizational Culture Model Based on the Balanced Scorecard at Kusuma Pertiwi Clinic - Roosi Rachma Kemala; A. Rohendi; R. Oke Andikarya (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Primary healthcare organizations require an integrated culture that can translate strategic objectives into consistent service behavior. This study developed an inter-organizational culture model using the Balanced Scorecard at Kusuma Pertiwi Clinic, Kediri Regency, East Java. A descriptive-exploratory qualitative case study was conducted through semi-structured interviews, non-participant observation, and document review involving seven key informants across managerial roles and generations. Data were analyzed using the Miles, Huberman, and Saldana model through data condensation, data display, conclusion drawing, triangulation, and member checking. The findings showed that the clinic's culture was anchored in family orientation, openness, discipline, flexibility, and honesty, but required stronger financial transparency, clearer role distribution, digital coordination, and structured accountability. The Balanced Scorecard analysis indicated good patient satisfaction and learning culture, while the financial and internal process perspectives required more systematic improvement. The proposed model integrates core cultural values, new professional values, operational mechanisms, collaborative leadership, and cross-generational mentoring to strengthen clinic performance.